Blended therapy for adolescents with chronic health conditions to increase fatigue-related self-efficacy (Booster): protocol for a single-case multiple baseline study - Maartje D. Stutvoet; Anouk Vroegindeweij; Jan Houtveen; Raphaële R. L. van Litsenburg; Elise van de Putte; Remco C. Veltkamp; Sanne L. Nijhof (Trials)
Abstract Background Fatigue is a common symptom in adolescents with a chronic health condition. Persistent fatigue and its impairments may be prevented by early intervention with Booster. Booster is a transdiagnostic blended care intervention that aims to increase fatigue-related self-efficacy (FSE). Through experience sampling methodology (ESM) via the Booster smartphone app, Booster helps users gain personalised insight into the relationship between their thoughts, feelings, activities, and fatigue. Based on this insight and shared-decision making, the participant and executive investigator set personal lifestyle goals, such as more exercise and fewer daytime naps. The previous version of Booster, PROfeel, has already been shown effective in treating persistent fatigue in youth. Booster’s value as an early intervention has yet to be studied. To better suit this aim and align with user preferences, the new Booster app includes features like goal attainment assistance, daily outcome tracking, and motivating game mechanics (e.g., rewards and a minigame). This protocol describes a study to examine the effect of Booster on FSE and the other study outcomes fatigue, school participation, life satisfaction, and perceived health. The secondary aim is to explore individual differences regarding (moment of) changes in outcomes during the Booster intervention. Methods It is a single-centre study with a multiple baseline single-case experimental design (SCED). We aim to include twenty adolescents ages 12 to 18 years with a chronic health condition and fatigue. Booster’s effect on outcomes will be measured with a daily survey during Phase A (baseline) and B (intervention). The start of phase B will be randomised across cases. The effect will be assessed with the multiple baseline single-case randomisation test (SCRT) at the group level. Additionally, at the single-case level, we will explore change using permutation distancing tests (PDTs), single-case interrupted time series analysis (ITSA), and change point analyses. Also, we will assess participant characteristics associated with (long-term) improvements. Discussion Booster uses innovative methods by combining tailored ESM-insight, mHealth and healthcare professional support. Group-level analysis, strengthened by single-case observational analyses, will evaluate the effectiveness of ESM-supported blended care as an early fatigue intervention and identify its potential working mechanisms. It lays the groundwork for implementing ESM tools in clinical practice. Trial registration ClinicalTrials, NCT06562335. Registered on 24 July 2024, https://clinicaltrials.gov/study/NCT06562335 .